A comparative study of antioxidant activity between black tea from Rwandan highlands with green and oolong teas from China. (9th February 2009) - Nkubana, Andrew; He, Qian
Antioxidant activity of the aqueous extract of black tea from Rwandan highlands was compared with that of green and oolong teas from China and was determined by use of 2, 2-diphenyl-1-picrylhydryzyl (DPPH) radical scavenging method. The higher the concentration of the extract, the higher was free radical scavenging activity. Antioxidant activity of the teas extracts decreased in the order: green > oolong > black. The extraction methods were hot water method, methanolic method and ethyl acetate method. The hot water method gave the highest yield in all teas extraction methods. The phenolic content of all teas extracts were analysed according to the Folin?ciocalteu method and were expressed as mg gallic acid equivalents/g of dry extract. Green tea, oolong tea and black tea extracts showed the highest phenolic content of 162, 144 and 124 mg GAE/g dry extract, respectively.